Response of green lacewing Chrysoperla carnea (Stephens) to various densities of Ephestia cautella (walk)eggs (Baghdad Science Journal, 2014)
Results of exposure larvae of the most important predator in the integrated pest management , the green lacewings, Chrysoperla carnea (Stephens) to various densities of fig moth Ephestia cautella eggs showed increasing in the number of consumed prey at decreasing rate of increasing prey density where curve slope consumption decreased gradually until leveling off. These specifications concurred with type II functional response that predators appear towards varied densities of its preys ,that was confirm by logistic regression between the proportion of prey eaten in relation to prey offered . Third larval instars of the predator showed attack rate (a) of 4.85. This was greater than the second larval instar (3.58). Handling time (Th) per prey decreased as the predator aged , it was 0.0046 day for the second larval instar and 0.0041 day for the third larval instars. The greatest theoretical maximum number of moth eggs to be consumed was 244 eggs/day for the third larval instar followed by second larval instars as 217 eggs/day, respectively.